A review of the safety aspects of radio frequency ablation. (1st September 2015) - Bhaskaran, Abhishek; Chik, William; Thomas, Stuart; Kovoor, Pramesh; Thiagalingam, Aravinda
Abstract: In light of recent reports showing high incidence of silent cerebral infarcts and organized atrial arrhythmias following radiofrequency (RF) atrial fibrillation (AF) ablation, a review of its safety aspects is timely. Serious complications do occur during supraventricular tachycardia (SVT) ablations and knowledge of their incidence is important when deciding whether to proceed with ablation. Evidence is emerging for the probable role of prophylactic ischemic scar ablation to prevent VT. This might increase the number of procedures performed. Here we look at the various complications of RF ablation and also the methods to minimize them. Electronic database was searched for relevant articles from 1990 to 2015. With better awareness and technological advancements in RF ablation the incidence of complications has improved considerably. In AF ablation it has decreased from 6% to less than 4% comprising of vascular complications, cardiac tamponade, stroke, phrenic nerve injury, pulmonary vein stenosis, atrio-esophageal fistula (AEF) and death. Safety of SVT ablation has also improved with less than 1% incidence of AV node injury in AVNRT ablation. In VT ablation the incidence of major complications was 5–11%, up to 3.4%, up to 1.8% and 4.1–8.8% in patients with structural heart disease, without structural heart disease, prophylactic ablations and epicardial ablations respectively. Vascular and pericardial complications dominated endocardial and epicardial VT ablations respectively. Up to 3% mortality and similar rates of tamponade were reported in endocardial VT ablation. Recent reports about the high incidence of asymptomatic cerebral embolism during AF ablation are concerning, warranting more research into its etiology and prevention. Highlights: The rates of major complications in RF ablation are listed below. In AF ablation it has decreased from 6% to less than 4%. Less than 1% incidence of AV node injury in AVNRT ablation. 5–11% in VT ablations of structural heart disease. 4.1–8.8% in epicardial VT ablations.